Pengaruh Kepemilikan Institusional, Kepemilikan Manajerial, Inventory Turn Over Dan Leverage Terhadap Net Profit Margin - Mitha Hadi Safitri; Sri Yuni; Christina Fransiska (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the effect of institutional ownership, managerial ownership, inventory turnover and leverage on net profit margin. This study uses a type of quantitative research using secondary data in the form of financial reports. In this study, the population is companies in the consumer goods industry sector that are listed on the IDX for the 2019-2021 period using a purposive sampling technique. Based on this technique, 48 companies were obtained with a span of 3 years of observation, so that 144 observation data were obtained. The data that has been obtained is then analyzed using the SPSS. The results of this study indicate that partially the institutional ownership, managerial ownership and inventory turnover variables have no effect on the net profit margin. Meanwhile, leverage has a negative and significant effect on net profit margin. Simultaneously the independent variables in this study, namely institutional ownership, managerial ownership, inventory turnover and leverage, together have no effect on net profit margin